Children's Connectedness with Siblings and Friends from Early to Middle Childhood during Play. Issue 8 (17th November 2022) - Leach, Jamie; Howe, Nina; DeHart, Ganie
ABSTRACT: The purpose of the present study was to investigate children's connected communication during play with a sibling and friend from early to middle childhood. Participants included 65 4-year-old focal children at time 1 (T1) and 46 7-year-old focal children at time 2 (T2) who were videotaped at home in separate semi-structured free play sessions with an older or younger sibling and a same-aged friend at both time points. Data were coded for connectedness in communication (e.g., smooth and flowing or disjointed and fragmented) across relationship contexts and time. Research Findings : Focal children made more failed attempts at establishing connectedness and engaged in more self-talk with their siblings than with their friends, whereas they maintained connectedness more often with their friends. In terms of the partners' balance of participation, at T1 focal children ended connected interactions more often than their siblings, and the siblings engaged in more self-talk and unclear statements. In contrast, the balance of participation did not differ between friends at T1 and T2, nor did siblings differ at T2, suggesting friend partners made equal contributions to the play interactions, whereas developmental differences were apparent for siblings. Practice or Policy : The findings contribute to our understanding of developmental and relationship differences of children's connected communication during play from early to middle childhood. Parents and educators need to be aware that opportunities for connection and disconnection during sibling play are typical and provide experiences for children to practice communication skills.